PKM Pemutakhiran Data Penduduk di Desa Kukuh Kerambitan Tabanan: Indonesia - Ginantra, Ni Luh Wiwik Sri Rahayu; Yanti, Christina Purnama; Wulandari, Dewa Ayu Putri; Hendrawati, Theresia (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2023)
Kukuh Village is a village located in Kerambitan District, Tabanan Regency, Bali. Regional government has been promoting routine population data collection but most people do not yet have awareness of the importance of such data collection. Village population data stored in the Kukuh Village Information System is currently inaccurate, because the population of Kukuh Village is increasing every year, causing population data stored in the Kukuh Village Information System to be less accurate. Because of this, a population data update was carried out in Kukuh Village, Kerambitan, Tabanan. This program is realized in order to make population data on the official website of the Kukuh Village Information System accurate, up-to-date, integrated, of good quality so as to create accurate population data on the official website of the Kukuh Village Information System.